2020
DOI: 10.1093/jisesa/ieaa064
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Feeding Behavior of Tibraca limbativentris (Hemiptera: Pentatomidae) on Rice Using an Electropenetrography Waveform Library

Abstract: The rice stalk stink bug, Tibraca limbativentris Stål, damages plant stalks while feeding, making it one of the most important rice pests in South America. Because the feeding behavior of T. limbativentris has not yet been studied in rice, we investigated T. limbativentris stylet penetration (probing) in rice stalks. A waveform library was created using the new AC-DC EPG monitor with different levels of input resistance (Ri). Six different waveforms were recorded and correlated via histological studies and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Waveforms were further grouped into nonprobing, pathway, xylem sap ingestion, salivation and ingestion, and interruption phases ( Table 1 and Figure 1 , Figure 2 and Figure 5 ). In comparison with the waveforms recorded from Pentatomidae species, we found that the Rp2 waveform varied in different plant tissues, which is consistent with the DM2 waveforms of Dichelops melacanthus on maize seedlings [ 31 ] and Tibraca limbativentris on Rice [ 18 ]. For the cell rupture strategy employed by R. pedestris , it is hard to distinguish the waveform salivation from ingestion, so salivation/ingestion was defined together as Rp3, the same as the NV3 of Nezara viridula [ 32 ].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Waveforms were further grouped into nonprobing, pathway, xylem sap ingestion, salivation and ingestion, and interruption phases ( Table 1 and Figure 1 , Figure 2 and Figure 5 ). In comparison with the waveforms recorded from Pentatomidae species, we found that the Rp2 waveform varied in different plant tissues, which is consistent with the DM2 waveforms of Dichelops melacanthus on maize seedlings [ 31 ] and Tibraca limbativentris on Rice [ 18 ]. For the cell rupture strategy employed by R. pedestris , it is hard to distinguish the waveform salivation from ingestion, so salivation/ingestion was defined together as Rp3, the same as the NV3 of Nezara viridula [ 32 ].…”
Section: Discussionsupporting
confidence: 77%
“…The detailed waves and peaks of Rp3 are illustrated in Figure 4 . Cell-rupture strategy defined by Backus comprised of two different types of waveforms: salivation (cell laceration and maceration of cell tissues) and ingestion (short ingestion of lacerated/macerated cell contents) [ 13 ], which is true for Piezodorus guildinii [ 29 ], Halyomorpha halys [ 28 ], Dichelops furcatus [ 30 ], Euschistus heros [ 24 ], and Tibraca limbativentris [ 18 ]. However, the waveforms of salivation and ingestion are not clearly distinguished in the case of R. pedestris , so we defined salivation/ingestion as Rp3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the hemipteran pests in the Neotropics, stink bugs of the genera Tibraca and Oebalus (Hemiptera: Pentatomidae) represent a serious challenge for rice production (Pantoja et al, 1997; Didonet et al, 2001; Kruger & Burdyn, 2015). Tibraca limbativentris Stål is stem‐feeding and damages the plant in two ways: a salivary sheath is formed when ingesting the contents of xylem vessels, and cells get ruptured by laceration and maceration when ingesting the contents of parenchyma cells (Almeida et al, 2020). During its feeding process, this pest injects saliva and sucks out the contents of plant tissues, damaging the stem, which leads to yield reduction.…”
Section: Introductionmentioning
confidence: 99%